2009
DOI: 10.1590/s1677-55382009000500010
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of human spermatozoa to cryoinjury in repeated cycles of thaw-refreezing

Abstract: Objective: To study the resistance of human spermatozoa to cryoinjury in repeated cycles of thaw-refreezing by using the fast liquid nitrogen vapor method. Materials and Methods: Semen specimens were obtained from sixteen normal and oligozoospermic individuals who required disposal at the sperm bank. Five of them had testicular cancer. Specimens were thawed and an aliquot was removed for analysis. The remaining specimens were refrozen without removing the cryomedia. Repeated freeze-thaw cycles were performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…After processing, epididymal and testicular spermatozoa can be either used for ICSI or cryopreserved. Cryopreserved specimens are thawed and processed using the principles already described (30). Methods for selecting viable sperm for ICSI are currently available in cases immotile spermatozoa only are obtained after processing (27,31).…”
Section: Laboratory Processing Of Surgi-cally-retrieved Spermmentioning
confidence: 99%
“…After processing, epididymal and testicular spermatozoa can be either used for ICSI or cryopreserved. Cryopreserved specimens are thawed and processed using the principles already described (30). Methods for selecting viable sperm for ICSI are currently available in cases immotile spermatozoa only are obtained after processing (27,31).…”
Section: Laboratory Processing Of Surgi-cally-retrieved Spermmentioning
confidence: 99%
“…It has been reported that motile spermatozoa can be recovered after five refreezing and thawing rounds in normozoospermic samples, but only after two rounds in cases of oligozoospermia (Verza et al, 2009). Spermatozoa of infertile men were also found to be less resistant to damage during cryopreservation compared with spermatozoa from fertile men (Donnelly et al, 2001).…”
Section: Cryopreservation Of Spermatozoa For Assisted Reproductive Tementioning
confidence: 99%
“…Epididymal and testicular spermatozoa may be cryopreserved using protocols routinely used for ejaculated sperm. [2122] If sperm is found and frozen, thawing can be done at any time, thus obviating the need to organize two operations (oocyte and sperm retrieval) at the same day. Also, cryopreservation may be an interesting tool to spare left-over specimens that would be discharged after ICSI, especially if the treatment cycle does not result in a pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…To date, our cryopreservation technique for surgically retrieval sperm is the standard liquid nitrogen vapor method using TEST-yolk buffer and glycerol as cryoprotectants. [2122] Epididymal specimens are concentrated by washing before freezing, and testicular sperm are freed from the testicular parenchyma, i.e., testicular homogenates are frozen. Cryopreservation of few sperm into an empty zona pellucida and the use of stimulants before freezing may optimize results.…”
Section: Introductionmentioning
confidence: 99%